2013
DOI: 10.1007/s10198-013-0504-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lead time and visual aids in TTO valuation: a study of the EQ-VT framework

Abstract: BackgroundThe effect of lead time in time trade-off (TTO) valuation is not well understood. The purpose of this study was to investigate the effects on health-state valuation of the length of lead time and the way the lead-time TTO task is displayed visually.MethodsUsing two general population samples, we compared three lead-time TTO variants: 10 years of lead time in full health preceding 5 years of unhealthy time (standard); 5 years of lead time preceding 5 years of unhealthy time (experimental); and 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…(35) DCEs without adaption were applied in this study as an attempt build from valuation studies in other fields (e.g., conjoint analysis) and to measure health preferences in the community using the internet.…”
Section: Discussionmentioning
confidence: 99%
“…(35) DCEs without adaption were applied in this study as an attempt build from valuation studies in other fields (e.g., conjoint analysis) and to measure health preferences in the community using the internet.…”
Section: Discussionmentioning
confidence: 99%
“…In both sites, participants were randomized to one arm and one block of health states (n = 5). The TTO tasks in the standard arm were the same for the two sites but had some differences in the experimental arm which were reported elsewhere [21]. Only the data collected from the standard arm was used in the current study.…”
Section: Euroqol Group's Valuation Technologymentioning
confidence: 99%
“…In this case, the current valuation task would end and a new task for a different health state would start. How the x values changed has been reported elsewhere [21]. Briefly, the first two values of x were 15 and 10 years.…”
Section: Euroqol Group's Valuation Technologymentioning
confidence: 99%
“…Nowadays, due to developments in technology, online data collection has become very popular, as it can substantially reduce the costs of conducting a valuation study. Studies conducted by the EuroQol Group on the impact of administration mode on TTO data collection showed that group-based interviews and online data collection resulted in a substantially larger proportion of respondents stating their point of indifference after just one or two steps in the iteration procedure than one-on-one personal interviews [ 15 , 26 28 ]. Because this is a clear indicator for a reduction in task comprehension and/or engagement of the respondents, the recently developed EuroQol protocols continue to be based on one-on-one personal interviews.…”
Section: The Time Trade-off (Tto) Tasksmentioning
confidence: 99%